Modulation of muscle anabolism and gut microbiota by Polyporus umbellatus extract attenuates dexamethasone-induced muscle atrophy - Nguyen Bao Ngoc; Subeen Kim; Hye-Young Youn; Huitae Min; Tam Thi Le; Mauliasari Intan Rizki; Dae Won Kim; Kwang Hyeon Cha; Young Tae Park; Sang Hoon Jung; Myungsuk Kim (Applied Biological Chemistry)
Abstract To investigate the pharmacological mechanisms by extract of Polyporus umbellatus (PU) protects against dexamethasone (DEX)-induced muscle atrophy, focusing on its direct effects on muscle cell signaling, mitochondrial function, oxidative stress, and its indirect influence via gut microbiota modulation. In vitro, DEX-treated C2C12 myotubes were used to assess PU’s effects on cell viability, myotube morphology, myogenic/atrophy gene expression, Akt/mTOR/FoxO3a signaling pathways, mitochondrial function, and oxidative stress. In vivo, a DEX-induced muscle atrophy mouse model was employed to evaluate the efficacy of orally administered PU and L. gasseri (ATCC 19992) alone on muscle mass, strength, exercise performance, and gene expression. Gut microbiota composition was analyzed via 16 S rRNA sequencing, with predicted microbial enzyme functions and correlations to muscle parameters examined. In vitro, PU significantly attenuated DEX-induced C2C12 myotube atrophy, activated Akt/mTOR signaling, inhibited FoxO3a signaling, mitigated oxidative stress, and enhanced mitochondrial function. In vivo, PU dose-dependently improved grip strength, muscle mass, and exercise performance in DEX-treated mice, concurrently upregulating myogenic and mitochondrial biogenesis genes. PU treatment significantly modulated gut microbial diversity and composition, notably increasing L. gasseri abundance. Oral administration L. gasseri recapitulated PU’s protective effects on muscle phenotype, gene expression, and gut microbiota modulation. L. gasseri levels and predicted microbial D-lactate dehydrogenase activity correlated positively with muscle health. However, bioactivity-guided fractionation of PU did not identify a single predominant active compound. In conclusion, PU protects against glucocorticoid-induced muscle atrophy through a dual mechanism involving direct muscle-protective actions and beneficial modulation of the gut microbiota, partly mediated by enrichment and direct effects of L. gasseri. Graphical Abstract